Modelling a High Quality Education for International Students - I. L. Pluzhnik; F. H. А. Guiral (Образование и наука)
Introduction. The strive for high quality of Russian higher education, puts an emphasis on seeking the ways to improve it in the line with the topical Global educational agenda. In the context of this study provision of high quality education is defined as managing students experience in and out of the classroom as an integrative whole which is indispensable for maximising educational outcomes. Though Russian universities have a steady intake of international students on mobility programmes, there are not enough studies modelling the application of these dimensions in Russian academic setting. The current study seeks for the pathways to overcome this gap.Aim. The article is targeted to rethink the strategy of managing high quality education for international students and to work out and test an integrated model for the educational quality enhancement regarding two critical dimensions of their university training in curricular-related and co-curricular areas.Methodology and research methods. Mixed research methods were utilised. Individual interviews and a survey with close-ended and open-ended items were used to find out challenging issues impeding the development of high quality education offered in curricular and co-curricular related dimensions. Classroom observation, peer experts opinions and content analysis of the courses taught and their outcomes evaluation were applied at the University of Tyumen, being 5-100 project participant, to indicate the components, pedagogical toolkit and competencies for high educational quality of international students.Results and scientific novelty. The developed integrated model for high educational quality provision included the main interrelated curricular and co-curricular components of quality enhancement. They involved the designed up-to-date academic Russian course; teacher-student interactive support, socio-cultural and intellectual engagement such as “buddy” scheme studentto-student support, discussion workshops on intercultural awareness of students and teaching staff. Teaching methods of reflection, critical analysis, confirmatory feedback, communities, project-based and action oriented learning, group discussions, language tandems were proposed. Major competencies for international students’ curricular-based and co-curricular educational quality were suggested: critical reading and reflection, academic writing, negotiating, argumentation, logical cohesion, intercultural and cross-cultural awareness, conflict avoidance, tolerance to ambiguity.Practical significance. The integrated model can be applied for road-mapping the action plan of international policy at any university in Russia to provide high quality education for international students.